(3EOGQI GdeUGQa GdESdGejIs - (3hgjHI (B, (3Ndhajs ((3YeGf(B:s (3OGQ GdEYUGQ GdYdej ddfTQ hGdJhRjY,s, 2016)
(3jVe eGgjI GdHfhc GdESdGejI hNUGFUgG, CfhGY GdNOeGJ GdeUQajI GdESdGejI hGdhSGWI GdeGdjI aj GdeUGQa GdESdGejI, EOGQI GdSjhdI aj GdeUGQa GdESdGejI, CSHGH GdCReI GdeGdjI GdYGdejI cQDjI ESdGejI, GdfhGMj GdEjLGHjI aj GdJYGed GdeUQaj aj Xd eYGjjQ GdeMGSHI ddeDSSGJ GdeGdjI GdESdGejI, WHjYI GdJYGed GdeUQaj hCgejJg aj GdJfejI GdEbJUGOjI hGdELJeGYjI, eYGjjQ GdeMGSHI ddeDSSGJ GdeGdjI GdESdGejI(B.s
(3HHdjhZQGajG(B: (3U(B.249-257s
Keywords: (3GdEbJUGO GdESdGejs; (3GdHfhc GdESdGejIs; (3GdHfhc(B- (3JfXje hEOGQIs